93.7k views
0 votes
PLEASE I NEED IT NOW.....In order to solve for the variable in the equation 1-(x+2)+2x = 5(2x-5) - X, Mikel first applies the distributive property

Which equation is a result of this step?
O 1-X+2+2x– 10x-5-X
O 1-X-2+ 2x = 10x-25- X
O 1-X-1+2x = 10X-25- X
O 1-X-1+ 2x = 10x-5- X

2 Answers

5 votes

Answer:

b

Explanation:

i just did the test <33

User Michele Tonutti
by
5.1k points
1 vote

Answer:

1 -x -2 +2x = 10x -25 -x

Explanation:

1-(x+2)+2x = 5(2x-5) - X,

Distribute

1 -x -2 +2x = 10x -25 -x

User Kyw
by
4.3k points